A coupled CFD‐DEM investigation of suffusion of gap graded soil: Coupling effect of confining pressure and fines content - Liu, Yajing; Wang, Lizhong; Hong, Yi; Zhao, Jidong; Yin, Zhen‐Yu (International journal for numerical and analytical methods in geomechanics, 2020)
Suffusion involves fine particles migration within the matrix of coarse fraction under seepage flow, which usually occurs in the gap‐graded material of dams and levees. Key factors controlling the soil erodibility include confining pressure (p′) and fines content (Fc), of which the coupling effect on suffusion still remains contradictory, as concluded from different studies considering narrow scope of these factors. For this reason, a systematical numerical simulation that considers a relative wide range of p′ and Fc was performed with the coupled discrete element method and computational fluid dynamics approach. Two distinct macroresponses of soil suffusion to p′ were revealed, ie, for a given hydraulic gradient i = 2, an increase in p′ intensifies the suffusion of soil with fines overfilling the voids (eg, Fc = 35%), but have negligible effects on the suffusion of gap‐graded soil containing fines underfilling the voids (eg, Fc = 20%). The micromechanical analyses, including force chain buckling and strain energy release, reveal that when the fines overfilled the voids between coarse particles (eg, Fc = 35%) and participated heavily in load‐bearing, the erosion of fines under high i could cause the collapse of the original force transmission structure. The release of higher strain energy within samples under higher p′ accelerated particle movement and intensified suffusion. Conversely, in the case where the fines underfilled the voids between coarse particles (eg, Fc = 20%), the selective erosion of fines had little influence on the force network. High p′ in this case prevented suffusion.